A firm's activity in social media and its relationship with corporate reputation, firm size and firm performance - Mäkinen, Hanna (2015)
The significance of social media has increased greatly in the past few years, leading companies to increase their social media activity and also increase their interest in knowing whether it is genuinely worth being active on social media, including knowing the potential advantages. This study aims to examine the relationship between social media activity and three variables: reputation, firm size and firm performance. The study analyzes the relationships between the constructs but does not propose or discuss the direction, that is, the causal linkages, between the variables. The type of research conducted for this study is quantitative research; it is based on data that are collected from companies’ social media channels. The selected channels for this research are Facebook, Twitter, LinkedIn and YouTube. The data on corporate reputation are collected from secondary sources and are based on a survey of Finnish companies’ reputations and responsibilities, implemented by a company called TNS Gallup. The data for firm performance and firm size are collected from companies’ annual reports. The dependencies between different variables are examined by using the correlation analysis in IBM SPSS version 22. The results of this study suggest that there is no relationship between social media activity and corporate reputation. Therefore, it cannot be demonstrated that companies that are active on social media have better or worse reputations than those of companies that are not. However, a partial relationship is found between social media activity and firm performance. This research gives a good argument for the case that merely being active in different social media channels is not sufficient to enhance corporate reputation or financial performance. Even companies that are active on social media do not necessarily inherently experience positive reputations or healthy financial performance.